Relationship between facebook function usage and social cohesion, and the moderating effect of social group, among rural youth virtual communities in Malaysia - Sahharon, Hamizah (2016)
The focus of this study is to determine the moderating effect of social group on the relationship between Facebook functionality usage and social cohesion among rural youth virtual communities. This study focuses on 1Malaysia Wireless Village youths in Peninsular Malaysia. Specifically, the objectives of this research are to 1) determine the level of social cohesion among 1Malaysia Wireless Village rural youth virtual communities; 2) determine the frequency of Facebook functionality usage; 3) identify the significant Facebook functionality usage that most contribute towards the level of social cohesion; 4) test the moderating effect of social group on the relationship between Facebook functionality usage and the level of social cohesion. This study is imperative to understand the efficacy of Facebook usage among rural youth and the outcome of this study could aid in relevant parties in planning for future programmes that involve social cohesion among the youth in Malaysia. Additionally, this study has further looked into the Theory of Interdependence and the Theory of Self Identity by relating them to the motivation for Facebook functionality usage. This study involved a total of 400 rural youths living within 1Malaysia Wireless Villages in Perlis, Negeri Sembilan, Seremban and Terengganu. This study uses a quantitative method of distributing a set of questionnaires that were developed from previous research findings and instruments. About 30 respondents were selected during the pre-test. This study utilized both SPSS and AMOS for data analysis. Descriptive statistics were used to describe the socio-demographic background of the respondents, the frequency of Facebook functionality usage and the level of social cohesion among rural youth virtual communities. The rest of the analysis involving correlations and the moderation effect were done using the Structural Equation Modelling (SEM) in AMOS. Confirmatory Factor Analysis (CFA) and measurement model in SEM were used in this study to test the reliability and the validity of the constructed model (convergent and discriminant). SEM was utilised to identify the correlation coefficient between the frequent use of the five Facebook functionalities and the inclination towards enhancing social cohesion. Finally, a multi-group analysis was used to test the moderating effect of social group on the causal effect of frequent Facebook functionality usage on social cohesion among the rural youth virtual communities of 1Malaysia Wireless Village. The findings of this study have shown that the level of social cohesion among 1Malaysia rural youth Facebook virtual community was only moderate (M = 2.88), which was highly inclined by the respondent’s sense of togetherness (M = 2.94) and sense of belonging (M = 2.93) towards their virtual community. The most frequently used Facebook functionality among the rural youths of 1Malaysia Wireless Village has been Group (M=2.93) and Conversation (M=2.86). It was identified that the frequent use of Facebook functionality usage contributed about 76% towards the level of social cohesion, the frequent use of Conversation (β=0.415), Group (β=0.348), Identity (β=0.201) and Reputation (β=0.167) functionalities would influence the respondent’s perceived sense of social cohesion. The frequent use of Conversation functionality usage was seen as the most contributed factor towards these rural youth’s sense of social cohesion on Facebook. Furthermore, social group was discovered to have a moderating effect on the relationship between the frequency of Sharing and Reputation functionality on Facebook and enhancing rural youth’s sense of social cohesion, members of in-group felt a higher social cohesion towards their Facebook virtual community compared to the out-group.